Age and sex variation in visceral adipose tissue - Panchu, Pallavi; Bahuleyan, Biju; Babu, Rose; Vijayan, Vineetha (International Journal of Advances in Medicine, 2019)
Background: Adipose tissue mainly visceral fat is said to be harmful and acts as a harbinger of metabolic disorders. A changing trend is seen in the recent decades with decreasing incidence of metabolic disorders in men even though visceral fat is said to be higher in them. Sex hormones may influence the deposition pattern of adipose tissue. The aim of this study was to observe effects of age on visceral fat and to know if the difference in gender pattern of fat distribution is maintained throughout life or disappears after menopause. Methods: This cross-sectional observational study was conducted in Thrissur on 385 apparently healthy subjects using Omron body composition analyser. Data was analysed using SPSS 20.0 version. The tests employed were NOVA, independent samples t-test. Results: In each age group, men had significantly higher visceral fat than females. As age increased, visceral fat increased significantly in both genders. In each group, except for younger age groups, VF levels were equal in men and women. Conclusions: Visceral fat is higher in men and this difference is seen in all age groups. As age increases, visceral fat levels also increased in men and women. The distribution of visceral fat is such that a greater number of men have high to very high levels at a younger age group, a feature observed in women only in the peri and post-menopausal age. Adoption of an active lifestyle coupled with healthy diet should protect against onset of metabolic disorders.